EFFECT OF RESTRICTED MILK FEEDING ON THE GROWTH OF GOAT KIDS BEFORE WEANING (Indian Journal of Animal Production and Management, 2013)
A study was conducted to find out the effect of feed restriction before weaning on the growth of goat kids. Eight Jamunapari kids with average birth weight of 1.9 kg were selected from the college farm after deworming. The goat kids were divided in two groups. One group was reared under farm condition i.e. control group and other group as experiment group, to whom milk was restricted with normal asses of creep feeding. The study revealed that the weight gain and average daily gain were higher in experiment group than control. Therefore it can be concluded that restricted milk feeding encouraged solid feed consumption by goat kids with early adaptation for intake of solid foods.
Keywords: Milk feeding; Goat kids; Weaning